Geochemical Characteristics of the Metamorphic Rocks of the Pohorje Mountains - Hinterlechner-Ravnik, Ana; Moine, Bernard (Geologija, 1977)
An attempt is made to interpret the origin of the Pohorje metamorphic rocks on the basis of their geochemical features. A total of 187 rock samples was examined chemically and under a polarizing microscope. Taking into consideration the distribution of the major elements and some trace elements seven stratigraphic levels are admitted. Their geochemical patterns and petrogenetic grid are shown by graphical projections, enabling a comparison of the geochemical facies observed with those of preexisting sedimentary deposits and associated igneous rocks. Significant differences between the original parent rocks of the various stratigraphic levels have been found and thereby a restoration of the paleogeographic conditions of the region is given. Some similarities and differences between rocks of the Pohorje and the Saualpe regions have been noted. The problem of the eclogite-amphibolite relation arose. The composition of both metamorphic rocks as well as their distribution in the metamorphic levels indicate that the amphibolite has been derived from the eclogite.